Clinical and histological evaluation of increase in the residual ridge width using mineralized corticocancellous block allografts: A pilot study - Reza Shahmohammadi; Amir Moeintaghavi; Mehrdad Radvar; Habibollah Ghanbari; Nasrollah Saghravanian; Shabnam Aghayan; Sara Sarvari (Tabriz University of Medical Sciences, 2017)
Background. Lateral ridge augmentation is conventionally accomplished by means of autogenous bone grafts. However, due to its complications, the application of autogenous bone graft substitutes, e.g. mineralized corticocancellous allograft, is recommended. Methods. In the present study, twelve patients were included, with insufficient alveolar ridge widths in the designated sites for dental implant placement. During the primary surgery, mineralized corticocancellous block allografts were fixed in deficient sites with titanium screws and resorbable collagen membranes were used to cover the blocks. After a period of six months, a flap was raised and variations in ridge width values was measured. Finally, a micro-biopsy was obtained from the sites for histologic investigation prior to preparing them for subsequent implant placement. Results. All the applied blocks were incorporated into the underlying bone except for one. A statistically significant difference was seen between the average ridge widths before placing the allografts compared with that of implant placement stage (2.62±1.02 mm vs. 7.75±1.63 mm, respectively). Vital bone tissue was detected in all the histological specimens obtained from the interface of blocks and the underlying bone. Conclusion. The results suggest that mineralized corticocancellous block allografts might be used as scaffolds for bone growth and ridge width augmentation.